Mental health law in Peru: work in progress. Issue 4 (November 2014) - Jimenez, David; Eguiguren, Christina Alejandrina; Dougall, Dominic; Pliszka, Bartłomiej; Hall, Ian
Abstract : Mental health law in Peru is developing. The Peruvian Constitution enshrines important human rights principles in relation to people with mental health problems but the enactment of such principles into national legislation is very patchy. This means that people with mental health problems, especially those admitted to hospital, may not receive optimum care and may be at risk of having their human rights breached. In this article we consider how far the current national legislation meets these constitutional rights and what the legislation that is in development may ultimately achieve.